Eradicating Extreme Poverty Globally - Miluwi, Joshua 0. (Gyan Management Journal, 2014)
The problem of Eradicating Extreme Poverty has been analyzed in this article. All 193 members' countries of UN, USA/D and at least 22 international organizations have agreed to eradicate poverty half by 2015 in the first MDC. Developing countries have cut extreme Poverty in half since 2000. That milestone was not met in much of Africa and South Asia. According to World Bank report of 2011 more than 1 billion people Worldwide still live in extreme poverty. It is very important to find out a way to eradicate extreme poverty globally. For this reason USAID and other organizations have set up a goal to eradicate extreme poverty by 2030. So it is necessity to find, ways to eradicate extreme poverty globally. Some recommendations are added in this article.
Keywords: Extreme poverty; nutrition; population stability; Good governance; Global Cooperation